Makarchenkoia gen. nov., a new genus of Orthocladiinae (Diptera, Chironomidae) from Arctic - Krasheninnikov, Andrey B.; Vshivkova, Kristina A. (Zootaxa, 2024)
Using adult males, Makarchenkoia samoyedica gen. nov. et sp. nov. from Yugorsky, Yamal and Taimyr Peninsulas of Arctic region are described and figured. New genus is separated from other Orthocladiinae genera on the basis of the combination of the following characters: eyes bare, reniform, without dorsomedial extension, apex of antenna without apical or subapical seta, squama without setae, R4+5 ending distal to end of M3+4, acrostichals begin at the border with antepronotum, hooked, single-row near the pronotum, double-row closer to the middle of the mesonotum, pulvilli reduced, tergite IX is densely covered with spinous microtrichia, anal point is naked, microtrichia are located only at its base, but 0–2 setae are located laterally, gonocoxite with a relatively well-developed rounded or rectangular SVo covered short setae, IVo consists of a dorsal part in the form of a small protrusion and a ventral part in the form of a cushion, densely covered with short setae, TSa convex, virga weak. Currently, this genus includes two species: Makarchenkoia samoyedica sp. nov. from the Yugorsky, the Yamal and the Taimyr Peninsulas and M. nudisquama (Makarchenko et Makarchenko, 2003), comb. nov. from the Okhotsk Sea basin.